Discontinuous structure of regional and subregional urban systems: Nouvelle-Aquitaine, France (1800–2015). (April 2023) - Lalanne, Aurélie; Sundstrom, Shana; Garmestani, Ahjond
In the prevailing literature in urban economics, conducting research on urban systems at the national scale tends to provide an elegant but reductive approach to the functioning of these systems, assuming, in particular, that city size distributions are continuous. Based on an alternative framework drawing from research in ecology and complex adaptive systems, this article questions this approach by testing the discontinuity hypothesis within regional urban systems in France using two methods and long-term census data (1800–2015). We found that the distribution of city sizes over the 200+ years of population data from the Nouvelle-Aquitaine region was discontinuous for every year of data. The distributions consist of groups of similarly sized cities, separated by gaps (discontinuities) where there are no cities at all. The location and number of discontinuities were conservative over time, suggesting that the processes shaping size classes are conservative and largely independent of societal disturbances such as wars. The two methods used to identify discontinuities were highly congruent. Finally, the Nouvelle-Aquitaine region is comprised of three former regions, Aquitaine, Limousin and Poitou-Charentes, each of which also had discontinuous city size distributions with conservative structures over time. The study results question the traditional expectations about the growth and development of urban systems.